Binding stability of peptides to Co–Cr–Mo alloy affects proliferation and differentiation of osteoblast. Issue 4 (31st January 2022) - Migita, Satoshi; Wakabayashi, Keita; Yamazaki, Tomohiko
Abstract: Cobalt–chromium–molybdenum (CCM) alloys possess high corrosion‐resistant properties as well as good mechanical properties. Hence, the alloys are employed in medical implants such as artificial knee and hip joints, coronary stents, and removable partial dentures. To improve the biocompatibility of CCM alloys, we reported that CCM‐binding peptide (CBP) linked to cell‐adhesive motif Arg–Gly–Asp (RGD) improved the attachment of endothelial cells on CCM alloys. However, the stability of CBP adsorption on the alloy and its effect on osteoblast compatibility are still unclear. In this study, we evaluated the stabilization of the adsorption layer of CBP–RGD on CCM alloy surface and investigated the effect of CBP–RGD peptide on the proliferation and differentiation of the osteoblasts. CBP–RGD layer exhibited higher stabilization than the RGD adsorption layer for 7 days. In addition, the proliferation of osteoblast on CBP–RGD adsorbed alloy higher than that on RGD adsorbed alloy. Moreover, the calcification of cells cultured on the CBP–RGD adsorbed alloy was significantly higher than that of the cells on RGD adsorbed alloy. These findings indicate that the CBP binding was stable during the culture of osteoblasts on the CCM alloy. Abstract : Cobalt–chromium–molybdenum (CCM) alloy binding peptide (CBP) was evaluated the adsorption stability on the surface and investigated. RGD‐linked CBP formed a stable layer and provided scaffolding function during the culture of osteoblasts on the CCM alloy.